Neonatal Outcomes in Infants Born to Mothers with Chronic Pediatric Gynecological Disorders: A Clinicopathological Evaluation - Zubia Bugti, Falah Hassan Abid, Hassan Raza Heral, Muhammad Yousuf Memon, Shahneela Bhutto, Farah Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic pediatric gynecological disorders (CPGDs) such as congenital uterine anomalies, ovarian dysfunction, chronic pelvic inflammatory disease, and endometriosis often persist into adulthood, complicating reproductive outcomes. These conditions may adversely affect neonatal health by impairing placental development and intrauterine growth, yet data remain limited, especially in low- and middle-income countries. Objective: To evaluate neonatal outcomes in infants born to mothers with chronic pediatric gynecological disorders and to assess associated placental pathology. Methods: This prospective clinicopathological study was conducted at the Department of Obstetrics and Gynecology, Unit I, Sandeman Provincial Hospital/Bolan Medical College Hospital (SPHQ/BMCH), Quetta, and Faisal Masood Teaching Hospital, Sargodha, Pakistan, from March 2022 to April 2023. A total of 120 mother–infant pairs were included, with 60 in the study group (mothers with CPGDs) and 60 in the control group (mothers without CPGDs). Neonatal outcomes assessed included gestational age, birth weight, APGAR scores, NICU admissions, congenital anomalies, and perinatal mortality. Placental samples were examined histopathologically. Statistical analysis was performed using SPSS version 26.0, with significance set at p<0.05. Results: Neonates of mothers with CPGDs had higher rates of preterm birth (31.7% vs. 15.0%, p<0.05), low birth weight (36.7% vs. 18.3%, p<0.01), APGAR scores <7 at 5 minutes (20.0% vs. 8.3%, p<0.05), and NICU admissions (25.0% vs. 11.7%, p<0.05). Congenital anomalies were more frequent in the study group (6.7% vs. 1.7%, p<0.05). Perinatal mortality was also higher (8.3% vs. 3.3%, p<0.05). Placental pathology revealed increased chorioamnionitis (13.3% vs. 5.0%), villous immaturity (10.0% vs. 3.3%), and focal infarction (8.3% vs. 3.3%). Conclusion: Chronic pediatric gynecological disorders are associated with adverse neonatal outcomes, including prematurity, low birth weight, NICU admissions, congenital anomalies, and increased perinatal mortality. Placental abnormalities suggest impaired intrauterine environments as a major contributor. Early risk stratification, preconception counseling, and multidisciplinary care are essential to optimize outcomes in this high-risk group. Keywords: Pediatric gynecological disorders, neonatal outcomes, prematurity, placental pathology, congenital anomalies, perinatal mortality